The Structure-Forming Potential of Selected Polysaccharides and Protein Hydrocolloids in Shaping the Properties of Composite Films Using Pumpkin Purée - Monika Janowicz; Justyna Kadzińska; Agnieszka Ciurzyńska; Karolina Szulc; Sabina Galus; Magdalena Karwacka; Małgorzata Nowacka (Applied Sciences, 2023)
The work aimed to investigate the rheological properties and the gelling process of selected film-forming solutions obtained based on hydrocolloids, such as sodium alginate, highly methylated pectin, and soy protein isolate with the addition of pumpkin purée. It was found that both concentration of hydrocolloid and the addition of pumpkin purée affected the rheological parameters. The non-linear nature of the flow curves was demonstrated, which allowed the curves to be described using the Ostwald de Waele model. The addition of pumpkin purée and the concentration of the structure-forming substance affected the apparent viscosity of the composite film-forming solutions. Considering the applied parameters, only the gelation temperature of composite gelatin film-forming solutions with the addition of pumpkin purée was possible to determine. Additionally, degassing of the solutions with the addition of pumpkin purée resulted in the reduction of the aeration degree and smoothening of the edible films’ surface.